PECULIARITIES OF THE BUSINESS CYCLE IN THE MODERN WORLD ECONOMY - Vasylchenko S.М.; Vasylyuk M.M., M.M.; Mykhailyshyn, L.I. (The actual problems of regional economy development, 2021)
The article examines the possible factors of increasing the amplitude of cyclical recession in the developed countries of the world during the global financial crisis of 2008-2009 and the pandemic crisis of 2020 caused by COVID-19. The developed countries during the last periods of the business cycle began to experience greater economic recessions compared to other countries. It especially draws attention on itself that the developing countries and the countries with risky markets (emerging markets and the developing economies) continued economic growth during this time though with slower pace. And this requires a scientific explanation, as it has become commonplace to consider that developed economies are more competitive and stable than countries with risky markets and the developing countries. This phenomenon seems paradoxical, because after the Keynesian revolution over the past century, humanity has gained extensive experience in regulating national economies and it seemed to have learned to smooth the amplitude of cyclical fluctuations. In view of this, the purpose of the article is to substantiate the reason for the increase in the amplitude of cyclical fluctuations in countries with developed economies. The study used an empirical method, which included collecting information, observing the phenomenon and its analysis, hypothesizing and developing a theory that explains the modern phenomenon of cyclicality in a broader sense. The authors of the article propose and ground the hypothesis that the reason for the greater amplitude of cyclical recessions in the economies of the developed countries compared to other countries, except other things, there can be a significant difference in the structure of economies. The developed countries differ in a significant predominance of the tertiary sector. The tertiary sector is larger, it has bigger profitability and is able to generate more value added compared to other sectors of the economy, and also greatly reduce it during the periods of recession. Thus, the growth of the tertiary sector of the developed economies leads to strengthening of cyclical fluctuations during the economic cycle. To confirm this hypothesis, we calculated the Pearson correlation coefficient, which showed the existence of a high dependence between GDP dynamics and the size of the tertiary sector in the economy. Therefore, in the authors’ opinion, measures for countercyclical regulation of economies of the developed countries should be aimed primarily at the tertiary sector. This will help withstand global recessions, as the developed countries today are more often becoming generators of instability due to the growing financialization of their economies and the growth of the tertiary sector in general.